2014
DOI: 10.4037/ajcc2014536
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Catheter Setup for Glucose Control in Critically Ill Patients: A Randomized Controlled Trial

Abstract: Background Use of an arterial catheter to obtain hourly blood samples for intensive insulin therapy monitoring avoids causing patients the discomfort of repeated fingersticks. Returning the clearing volume may decrease procedure-related blood loss by 50% and minimize the risk of anemia. Objectives To compare the feasibility of 2 arterial catheter clearing-volume return setups for hourly blood extractions and to evaluate the related complications and the accuracy of arterial samples in determining glycemia.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 40 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Post hoc analysis after matching the burn area and wound score indicated that the ADRR was the only blood glucose index significantly associated with the mortality of patients <43 years of age ( P < 0.01). [118] Dahagam et al [115] also confirmed that in critically ill patients with severe burns, glycemic variability was higher among those who died than those who survived (26% [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] vs. 21%, [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , P < 0.05), and multiple regression analysis showed that high glycemic variability was associated with prolonged hospital stay ( P < 0.05). Thus, excessive blood glucose variability and frequency of blood glucose falling outside the normal range should be avoided.…”
Section: Target Blood Glucose Levels Among Critically Ill Patients Wi...mentioning
confidence: 88%
See 1 more Smart Citation
“…Post hoc analysis after matching the burn area and wound score indicated that the ADRR was the only blood glucose index significantly associated with the mortality of patients <43 years of age ( P < 0.01). [118] Dahagam et al [115] also confirmed that in critically ill patients with severe burns, glycemic variability was higher among those who died than those who survived (26% [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] vs. 21%, [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , P < 0.05), and multiple regression analysis showed that high glycemic variability was associated with prolonged hospital stay ( P < 0.05). Thus, excessive blood glucose variability and frequency of blood glucose falling outside the normal range should be avoided.…”
Section: Target Blood Glucose Levels Among Critically Ill Patients Wi...mentioning
confidence: 88%
“…Rationale : In critically ill patients, the sampling priority for glucose monitoring is arterial > venous > capillary. [27] A prospective observational study [28] found that the accuracy of arterial blood glucose values (69.9% and 76.5% with a glucose meter and a blood gas analyzer, respectively) was higher than capillary blood glucose values (56.8% and 56.8%, respectively). The accuracy of capillary blood glucose values was only 26.3%, and the accuracy of arterial blood glucose values measured with a glucose meter or a blood gas analyzer was 55.6% and 64.9%, respectively.…”
Section: Blood Glucose Monitoring In Critically Ill Patientsmentioning
confidence: 99%
“…Returning the clearing volume may substantially decrease procedure-related blood loss. 57 RaurellTorredàand colleagues 57 questioned whether arterial catheter setup influenced the rate of mechanical problems and catheter infection, and whether the glycemic values matched those obtained from venous samples. patients were randomized to either the intervention group (equipped with a nonwaste needleless setup) or the control group (equipped with the nonwaste syringe setup).…”
Section: Agitation Confusion and Deliriummentioning
confidence: 99%